Avaliação tomográfica da estabilidade volumétrica de áreas de reconstrução óssea alveolar após levantamento de seio maxilar com biomateriais heterógenos - Klein, Gustavo Batista Grolli (2012)
The aim of this study was to evaluate the imensional stability of the volume of bone substitute (bovine bone mineralization) after the elevation of the maxillary sinus membrane by means of computed tomography. We analyzed fifty-two postoperative CT scans, two of the maxillary sinus in a sample of thirteen patients who underwent reconstructive surgery sinus. The first was performed immediately after surgery (T0) and the second was made following eight months (T1). A total of twenty-six maxillary sinus was increased by filling bovine bone mineralization using the technique of access sidewall. The measurement of volume was performed by digital subtraction 3D software InVesalius ® 3.0. The increase in bone volume during the measured interval was observed in all patients. From the measurements derived from volumetric images was increased from 9.47% in regions. The average increase in boné volume between T (0) and T (1) was 0.17 cm3 (0.5 to 3.09 cm3, SD ± 6.98). The correlation coefficient between exchange of bone volume and elapsed time was statistically significant (p = 0.00001229). The average volume of the first CT T (0) was 1.37 cm3 (0.10 to 2.45 cm3, SD ± 0.56) and second tomography T (1) was 1.49 cm3 (0.10 - 2.48 cm3, SD ± 0.53 cm3). In the limit of the sample, this study demonstrated an increase in bone volume of bovine bone mineralization after elevation of the axillary sinus cavities with critical defects, confirming the ability of the bio-material to maintain its structure stable without resorption during the healing phase proposed by the manufacturer.